Bytový dům ve Valašském Meziříčí - Šindelek, Jiří (Vysoké učení technické v Brně. Fakulta stavební, 2016)
Zadáním diplomové práce bylo navrhnout a zpracovat projekt Bytového domu ve Valašském Meziříčí. Objekt je umístěn v centru města, kousek od nemocnice. Navržený objekt je umístěn ve svažitém terénu a je čtyřpodlažní podsklepený. Okolní zástavba je tvořena panelovými domy z minulého století. Záměrem bylo navrhnout bytový dům, který zapadne do okolní zástavby. V suterénu bytového domu se nachází technické zázemí a jednotlivé garážové stání. V nadzemních podlažích jsou navrženy bytové jednotky. V úrovni prvního nadzemního podlaží je navržena prodejna potravin ze severní strany. Zastřešení objektu je řešeno jednoplášťovou plochou střechou.

Theme of this thesis was to design and process a project of Apartment building in Valašske Meziříčí. The building is situated in the city center, close to hospital. Designed apartment building with four floors and a basement is located on a sloping terrain. Surrounding buildings are costisted of blocks of flats that were built in last century. Goal of the thesis was to design apartment house which will fit to the neighborhood. There are technical backround and parking slots in the basement of the bilding. Apartments are situated in above-ground floors. The grocery store lies on the northern side of the building on the same level as first floor. The apartmen building is covered by single-skinned flat roof.
Residential building in Valašské Meziříčí
Keywords: Bytový dům; prodejna potravin; plochá střecha; pochůzí terasy; garáže; Apartment house; grocery store; flat roof; walkable terrace; parking slots